PEMBINAAN PENDIDIKAN AGAMA ISLAM DI LAPAS WANITA: PEMBINAAN PENDIDIKAN AGAMA ISLAM DI LAPAS WANITA - Pasaribu, heka afriannur (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
Religious knowledge is something that every human being must know. This is needed to carry out daily worship. The sources of Islamic law are the Al-Qur'an and the Sunnah of the Prophet. Worshiping Allah is the obligation of every Muslim. Muslims who obey Allah SWT will find peace in the world and will enter heaven in the next day. The counseling carried out in this women's prison is able to increase the motivation and awareness of every woman in the prison to focus more on worshiping Allah. Increase their knowledge about the pillars of prayer, the conditions for valid prayer and what things invalidate prayer. And also increase their awareness of doing dhikr after every prayer and dhikr in daily activities. It is hoped that this increase in knowledge will provide peace of mind to the women in prison. Motivate them for their life after leaving prison. Key words: education, religion, dhikr, women